(untitled) (Studia theodisca, 2021)
The Other Side narrates the story of an anachronistic regime built up in Asia with remains of Decadent Europe. Before its collapse, due to the impossibility of existing against history and nature, the narrator concludes: «The demiurge is a hybrid». This paper studies the identity of the demiurge in order to clarify the meaning of this alienating statement. In doing so, it recognizes that the extraordinary regime reflects many features of the Habsburg myth; and also, that as an “experiment of Austria” it needs to take place elsewhere, where the western repressed dreams of power can be fulfilled: in a colony.